(untitled) (Dimensión Antropológica, 2022)
The history of the steam machines is very important to understand industrialization in our country. This technology was used to propel the utmost important industry. Mining exploitation was the most dynamic economic activity. In this essay, I analyse the initiatives to obtain and to put to work those machines with the main purpose of draining the mines. Because of warlike actions during the war of independence, they were flooded. The use of this technological innovation intended to reverse the war’s negative effects and to lure enough capital to rescue the productive process that produced richness, employment, commerce and incomes to the new Estate.